Matchmaker [videorecording (DVD)] - Joffe, Mark, 1956-; Janszen, Karen; Nowra, Louis, 1950-; Linehan, Graham; Garofalo, Janeane; Leary, Denis; O'Hara, David, 1965-; O'Shea, Milo, 1926-2013 (Universal, 2002)
Marcy heads to a wee quaint Ireland burgh during its annual matchmaking festival, where she finds love and humanity amid the beer-guzzling, blarney-slinging locals.